An automated voxelized dosimetry tool for radionuclide therapy based on serial quantitative SPECT/CT imaging. Issue 11 (10th October 2013) - Jackson, Price A.; Beauregard, Jean‐Mathieu; Hofman, Michael S.; Kron, Tomas; Hogg, Annette; Hicks, Rodney J.
Abstract : Purpose: : To create an accurate map of the distribution of radiation dose deposition in healthy and target tissues during radionuclide therapy. Methods: : Serial quantitative SPECT/CT images were acquired at 4, 24, and 72 h for 28 177 Lu‐octreotate peptide receptor radionuclide therapy (PRRT) administrations in 17 patients with advanced neuroendocrine tumors. Deformable image registration was combined with an in‐house programming algorithm to interpolate pharmacokinetic uptake and clearance at a voxel level. The resultant cumulated activity image series are comprised of values representing the total number of decays within each voxelˈs volume. For PRRT, cumulated activity was translated to absorbed dose based on Monte Carlo‐determined voxel S‐values at a combination of long and short ranges. These dosimetric image sets were compared for mean radiation absorbed dose to at‐risk organs using a conventional MIRD protocol (OLINDA 1.1). Results: : Absorbed dose values to solid organs (liver, kidneys, and spleen) were within 10% using both techniques. Dose estimates to marrow were greater using the voxelized protocol, attributed to the software incorporating crossfire effect from nearby tumor volumes. Conclusions: : The technique presented offers an efficient, automated tool for PRRT dosimetry based on serial post‐therapy imaging. Following retrospective analysis, this method of high‐resolution dosimetry may allow physicians to prescribe activity based on required dose to tumor volume or radiation limits to healthy tissue in individual patients.